Al-Siyāq al-Qur’ānī wa Aṣaruhu ‘Inda al-Qādī Ibn ‘Aṭiyyah fī al-Taujīh al-Nahwī (Dirāsah Tafsīriyyah Nahwiyyah) - Husain, Muhammad Zakir; Kurniawan, Cecep Soleh (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2020)
إن هذا البحث يتحدث عن القاضي ابن عطية والسياق القرآني وأهميته وأثره عند القاضي ابن عطية في توجيه الإعراب في تفسيره المسمى المحرر الوجيز في تفسير الكتاب العزيز، والسياق بحث عن بيان الكلمة أو الجملة القرآنية منتظمة مع ما قبلها وما بعدها في الجملة، وتتسع دائرته فيشمل الجمل السابقة واللاحقة، بل والسورة، والكتاب كله. والبحث يتضمن ثلاثة مباحث: المبحث الأول: لمحة موجزة عن حياة القاضي ابن عطية، والمبحث الثاني: دراسة نظرية عن السياق القرآني، والمبحث الثالث: دراسة تطبيقية نقدية أي أثر السياق القرآني في التوجيه النحوي وتطبيقه عند القاضي ابن عطية ومقارنة ما ذهب إليه ورجح إليه معتمدا على السياق القرآني مع غيره من المفسرين. فالبحث جار على الدراسة النظرية التطبيقية النقدية. ويعني بها دراسة نظرية عن السياق القرآني وتطبيقه عند القاضي ابن عطية في التوجيه النحوي، ومناقشة آرائه وترجيحه في التفسير معتمدا على السياق القرآني مع غيره من المفسرين. ونتيجة البحث تدل على أن القاضي ابن عطية هو الإمام العلامة، شيخ المفسرين، القاضي أبو محمد عبد الحق بن غالب بن عبد الرحمن بن غالب بن عبد الرؤوف بن تمام بن عبد الله بن تمام بن عطية بن خالد بن عطية المحاربي الداخل، والسياق القرآني مقصورة على سياق المقال ولا يشتمل على سياق الحال أو المقام، ومدي أهمية القاضي ابن عطية في تطبيق السياق القرآني في تفسيره المسمى بالمحرر الوجيزفي تفسير الكتاب العزيز فيThis research speaks about al-Qa>di> ibn Atiyyah and the Qur’anic context, its importance, and its impact on Ibn Attiya in directing the parsing in his interpretation called the brief editor in the interpretation of the Holy Book. Then in the sentence, its circle widens to include the previous and subsequent sentences, and even the surah and the whole book. The research includes three topics: The first topic: a brief overview of the life of Judge ibn Atiyyah, and the second topic: a theoretical study on the Quranic context, and the third topic: a critical applied study that is the effect of the Quranic context in the grammatical guidance and its application to Judge ibn Atiyyah and a comparison of what he went to and was likely to be dependent In the context of the Qur'an with other interpreters. The research is ongoing on the critical applied theoretical study. By this, it means a theoretical study on the Quranic context and its application to Judge ibn Atiyyah in grammatical guidance, and the discussion of his views and weighting in interpretation based on the Quranic context with other interpreters. And the result of the research indicates that Judge ibn Atiyyah is Imam al-Allamah, Sheikh of the interpreters, Judge Abu Muhammad Abdul Haq Bin Ghaleb Bin Abdul Rahman Bin Ghaleb Bin Abdul Raouf Bin Tammam Bin Abdullah Bin Tammam Bin Atiyah Bin Khalid Bin Atiyah Al-Muharbi Al-Dakhel, and the Quranic context is limited to The context of the article does not include the context of the situation or the place, and the extent of the importance of Judge Ibn Attiya in applying the Qur'anic context in his interpretation called Al-Wujazevi interpretation of the dear book in grammar. Tulisan ini membahas mengenai al-Qa>di> ibn Atiyyah, konteks al-Qur’an, pentingnya dan penerapannya dalam tafsir al-Muharrir al-Waji>z fi> al-Kita>b al-Azi>s yang lebih popular dengan nama tafsir al-Muharrir al-Waji>z, yang dikarang oleh ibn Atiyyah dalam hal pandangan-pandangannya terkait konteks dan kedudukan suatu kata dalam nahwu yang memberikan pengaruh terhadap perbedaan penafsiran al-Quran. Konteks al-Qur’an adalah penjelasan lafadz atau frasa dalam suatu ayat dengan tidak keluar dari makna ayat sebelum dan sesudahnya, baik dalam satu ayat, satu tema, satu surah atau dalam keseluruhan ayat dalam al-Qur’an. Ada tiga hal yang akan dibahas. Pertama: Sejarah ringkas kehidupan al-Qa>di> ibn Atiyyah. Kedua: kajian teori mengenai makna siyaq al-Qur’an, dan yang ketiga Penerapan siya>q al-Qur’a>n dalam kaitannya nahwu dan makna dalam al-Qur’an, dengan mengungkap penerapan siyaq al-Qur’an oleh al-Qa>di> ibn Atiyyah dan membandingkan dengan penerapan siya>q al-Qur’a>n oleh ulama-ulama tafsir lainnya. Kajian ini mengenai teori konteks al-Qur’an dan penerapannya dalam tafsir al-Muharrir al-Waji>z yang dikarang oleh ibn Atiyyah. Hasil dari kajian ini adalah konteks al-Qur’an hanya terbatas pada siya>q maqa>li dan tidak termasuk siya>q al-ha>l atau al-Maqam, serta pengaruhnya yang besar dalam penerapan dan penggunaan konteks al-Qur’an dalam tafsir al-Qa>di> ibn Atiyyah.